UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR DALAM PEMBELAJARAN PADA SD NEGERI 4 SIGLI - Mustafa (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This purpose of this research is to increase students’ interest at the elementary level of SD Negeri 4 Sigli by using Pictures in learning Indonesian Language. The type of researched was Classroom Action Research (CAR). The object of the research was the students’ interest at SD Negeri 4 Sigli using pictures as media. The technique of collecting data was observation. The observation was used to identify the fact about students’ interest. The data Analysis used was qualitative description and percentage of students’ learning interest. The result showed that through pictures media the students’ learning interest increased. The earlier observation had 50 %. After doing treatment in cycle 1 the mean value was only 51,1. Most of the students still got lower value in learning achievements and also below the standard criteria i.e. 75 %. Thus it had to be continued to the next cycle. In the cycle II the students’ mean value increased 98,12 %. Most students got highest score in this cycle i.e. 100%. The conclusion was the use of pictures media gave the improvement in students’ learning at SD Negeri 4 Sigli.